Cold Fusion: Massive Karyotype Evolution in the Antarctic Bullhead Notothen Notothenia coriiceps. Issue 7 (1st July 2017) - Amores, Angel; Wilson, Catherine A; Allard, Corey A H; Detrich, H William; Postlethwait, John H
Abstract: Half of all vertebrate species share a series of chromosome fusions that preceded the teleost genome duplication (TGD), but we do not understand the causative evolutionary mechanisms. The "Robertsonian-translocation hypothesis" suggests a regular fusion of each ancestral acro- or telocentric chromosome to just one other by centromere fusions, thus halving the karyotype. An alternative "genome-stirring hypothesis" posits haphazard and repeated fusions, inversions, and reciprocal and nonreciprocal translocations. To study large-scale karyotype reduction, we investigated the decrease of chromosome numbers in Antarctic notothenioid fish. Most notothenioids have 24 haploid chromosomes, but bullhead notothen ( Notothenia coriiceps ) has 11. To understand mechanisms, we made a RAD-tag meiotic map with ∼10, 000 polymorphic markers. Comparative genomics aligned about a thousand orthologs of platyfish and stickleback genes along bullhead chromosomes. Results revealed that 9 of 11 bullhead chromosomes arose by fusion of just two ancestral chromosomes and two others by fusion of three ancestral chromosomes. All markers from each ancestral chromosome remained contiguous, implying no inversions across fusion borders. Karyotype comparisons support a history of: (1) Robertsonian fusions of 22 ancestral chromosomes in pairs to yield 11 fused plus two small unfused chromosomes, like N. angustata ; (2) fusion of one of the remaining two ancestral chromosomes to a preexisting fused pair, giving 12 chromosomes like N. rossii ; and (3) fusion of the remaining ancestral chromosome to another fused pair, giving 11 chromosomes in N. coriiceps . These results raise the question of what selective forces promoted the systematic fusion of chromosomes in pairs and the suppression of pericentric inversions in this lineage, and provide a model for chromosome fusions in stem teleosts.